Factors related to the presence of mosquito eggs trapped in ovitraps DHF-endemic areas in Kendari City, Indonesia - Askrening, Askrening; Supryatno, Adi; Yunus, Reni; Supiati, Supiati (YCAB Publisher & IAKMI SULTRA, 2021)
Background: Dengue hemorrhagic fever (DHF), one type of infectious disease caused by the dengue virus, is still becoming a public health problem in Indonesia. The high number of dengue cases in Indonesia, especially in Kendari City itself, is closely related to environmental conditions, especially when it is known that the city has entered the rainy season.Objective: This study aimed to identify and analyze the factors associated with the presence of mosquito eggs trapped in ovitraps DHF-endemic area in Kendari City, Indonesia.Methods: This study used an analytic observational approach with a cross-sectional design. The research sample in this study was 50 houses located in endemic areas of Kendari selected using simple random sampling. Data were collected by observation using a checklist sheet and direct observation in each room of the respondent's house based on lighting, temperature, humidity, and physical environmental conditions, as well as the presence of mosquito eggs or larvae trapped in the ovitrap. The analysis was carried out in two stages, namely univariate analysis and bivariate analysis using the Chi-Square test.Result: From 50 houses observed, 13 houses (26%) had the presence of mosquito eggs, 42 houses (84%) had bad air temperature, 19 houses (38%) had poor humidity, and 35 houses (70%) had a higher frequency. In addition, the temperature, lighting, and environmental conditions did not have a significant relationship with the presence of mosquito eggs in ovitraps in endemic areas of Kendari City, with p-values of 0.94, 0.52, and 0.39, respectively. In contrast, the humidity factor has a significant relationship with the presence of eggs with a p-value of 0.000.Conclusion: There was a significant relationship between humidity and the presence of mosquito eggs in ovitraps in endemic areas of Kendari City, Indonesia. It is recommended that residents increase Mosquito Nest Eradication (PSN) activities, perform selective abatization, and disseminate information about DHF through counseling or other activities conveyed through health workers with full support from community leaders and adjusted to the level of education of the local population.